Novel Therapeutic Approaches to Control Fungal Biofilms - Guisso, Luigi Pedrini [UNESP]; Ribeiro, Natália Pereira [UNESP]; Carmona, Wilmer Ramírez [UNESP]; Roseno, Ana Carolyna Becher [UNESP]; Pessan, Juliano Pelim [UNESP]; Monteiro, Douglas Roberto [UNESP] (Springer Nature, 2025)
Fungal biofilms pose a significant threat to healthcare services globally due to their distinct pathogenic features, as numerous fungal species lead to local and/or systemic diseases, primarily in immunocompromised individuals. Some of these fungal infections vary from illnesses compromising skin and nails to candidiasis (oral or vaginal) and pulmonary infections. Tolerance to major antifungal drugs by some fungal biofilms is reported worldwide, without discrimination between low- and high-income countries, which complicates the management of biofilm-related diseases. This scenario has stimulated the study and development of novel therapeutic approaches to control fungal biofilms, which include new antifungals, drug combinations, photodynamic therapy, immunotherapy with antibodies and vaccines, antimicrobial peptides, phage therapies, nanotherapies, and the recent use of natural compounds. This chapter discusses these therapies in detail and presents updated data on their efficacy, safety, mechanisms of action, and possible clinical applications.